2019
DOI: 10.1186/s13765-019-0441-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cuticular waxes on permeation of fungicides azoxystrobin and chlorothalonil into apples

Abstract: Time-dependent permeation characteristics of two fungicides azoxystrobin and chlorothalonil into apples were investigated in the presence and absence of the cuticular waxes. Either apple samples which were subjected to waxremoving treatment or not (raw) were individually submerged in each dilution solution of the tested fungicides for a short time, and some of each submerged sample were then washed in running tap water. All apple samples were incubated under controlled conditions and collected sequentially aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, chlorothalonil is known to be used in post-harvest treatment as a chemical control agent [29]; thus, it is expected that it can be used to yield high detection rate in apples. However, the results of one study indicated that residual chlorothalonil was significantly removed from the apple surface after washing [30]. Watermelons and cucumbers are classified as cucurbits, and chlorothalonil is used to protect against gummy stem blight, powdery mildew, and anthracnose infections [31].…”
Section: Application Of Developed Methods In Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chlorothalonil is known to be used in post-harvest treatment as a chemical control agent [29]; thus, it is expected that it can be used to yield high detection rate in apples. However, the results of one study indicated that residual chlorothalonil was significantly removed from the apple surface after washing [30]. Watermelons and cucumbers are classified as cucurbits, and chlorothalonil is used to protect against gummy stem blight, powdery mildew, and anthracnose infections [31].…”
Section: Application Of Developed Methods In Monitoringmentioning
confidence: 99%
“…These five products were analyzed to confirm the presence of non-detected target pesticides and used for method validation. Agricultural products for the monitoring of chlorothalonil were collected from Seoul (47), Busan (43), Incheon (35), Daegu (31), Daejeon (24), Suwon (20), Ulsan (20), Gwangju (20), Cheongju (16), Changwon (18), Wonju (14), Jeju (12), Jeonju (10), and an online market (30) in Republic of Korea. A total of 15 commodities were selected for monitoring, and 340 samples were collected from local markets: vegetables (154), fruits (91), potatoes (47), cereals (34), and legumes (14).…”
Section: Sample Selection and Collectionmentioning
confidence: 99%
“…It also reduces the infestation of some pests and diseases [7] and enhances the mechanical strength of grape peel [8]. However, some studies have proposed that the waxy layer structure on the surface of fruits may provide a way for hydrophobic pesticides to penetrate plant tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, some experiments yield the opposite results. For example, the concentration of azoxystrobin in washed apples was lower in samples with wax removed than in samples without wax extracted from the cuticle [9]. Pesticide residues on citrus and waxed apples are primarily concentrated in the epidermal wax [28,29], which is thought to be because those pesticides may dry on the surface or bind to the wax outside the peel and then adhere to the peel, thus remaining nonremovable in the wash treatment [30].…”
Section: Introductionmentioning
confidence: 99%
“…The cuticle characteristics of apples can be affected by various factors, such as the plant cultivar, treatment with 1‐methylcyclopropene (1‐MCP) and storage conditioning, (Matas et al ., 2011; Hwang et al ., 2019). However, most of these studies focused on a specific duration of storage or a single developmental stage (Lara et al ., 2019), and little is known about changes in combined wax and cutin compounds in postharvest apple fruit.…”
Section: Introductionmentioning
confidence: 99%